Design and Strength Simulation of a Modular Auxiliary Inverter - WANG Zhipeng; LI Yan; XU Mingxia (机车电传动)
The auxiliary inverter is an important part of the railway vehicles. Its performance directly affects the normal operation of the vehicle. A modular design of the auxiliary inverter was introduced. The structure of each function module was expounded. And structural strength and modal of the converter were analyzed by using the finite element simulation software ANSYS, and the structure was optimized according to the results. The generality and the production efficiency were improved, and good integration, reliability, and also maintainability can be obtained through the modular design.